2010
DOI: 10.1371/journal.pone.0010846
|View full text |Cite
|
Sign up to set email alerts
|

A Chemical Genetic Screen for Modulators of Asymmetrical 2,2′-Dimeric Naphthoquinones Cytotoxicity in Yeast

Abstract: BackgroundDimeric naphthoquinones (BiQ) were originally synthesized as a new class of HIV integrase inhibitors but have shown integrase-independent cytotoxicity in acute lymphoblastic leukemia cell lines suggesting their use as potential anti-neoplastic agents. The mechanism of this cytotoxicity is unknown. In order to gain insight into the mode of action of binaphthoquinones we performed a systematic high-throughput screen in a yeast isogenic deletion mutant array for enhanced or suppressed growth in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 39 publications
3
33
0
Order By: Relevance
“…These results are similar to those obtained by Emadi et al [22], who evaluated the possible mechanism of action of bis-naphthoquinones and concluded that these compounds cause membrane depolarization.…”
Section: Discussionsupporting
confidence: 91%
“…These results are similar to those obtained by Emadi et al [22], who evaluated the possible mechanism of action of bis-naphthoquinones and concluded that these compounds cause membrane depolarization.…”
Section: Discussionsupporting
confidence: 91%
“…Mitochondrial electrochemical potential is correlated with the fluorescence intensity of Rho-123 (when decreased fluorescence means loss of the mitochondrial electrochemical potential) [42] . Flow cytometry was performed using a FACSCalibur (Becton Dickinson, San Jose, CA, USA) with excitation at 488 nm and emission read using a 525-to 550-nm filter (FL1).…”
Section: Assay Of the Electrochemical Potentialmentioning
confidence: 99%
“…Mechanistic studies using a chemical genetic screen in yeast revealed that their cytotoxicity was probably related to their ability to undergo redox cycling, produce free radicals and cause mitochondrial dysfunction. 4 …”
Section: Introductionmentioning
confidence: 99%